Back from the past: Molecular and morphological support for Simulium mutucuna Nunes de Mello & Vieira da Silva, 1974 (Diptera: Simuliidae) as a valid species - Nascimento, Jeane M.C. (2021)
Simulium mutucuna, a species described based on a single female from Roraima state, was previously synonymized with Simulium paynei and currently is considered a synonym of Simulium rubrithorax. In the present paper we present morphological and molecular evidence supporting the validity of S. mutucuna based on analysis of specimens from Brazil, Venezuela and Mexico. We redescribe the female and describe, for the first time, the male, pupa and larva of S. mutucuna and discuss the morphological differences between this species and the others that are already considered as its senior synonyms. Currently, the distribution of S. mutucuna is restricted to Roraima state. The distribution record for S. rubrithorax in Brazil’s North region needs to be removed, since the previous records were based on occurrence of S. mutucuna. Finally, we present new evidence of cryptic diversity in the S. paynei complex based on molecular information.